The question is, whether the following series is convergent, absolutely convergent or divergent $$\sum_{n=1}^\infty \frac{(-1)^{n+1}}{2n-1}.$$

  1. The term $\dfrac{(-1)^{n+1}}{2n-1}$ = $ \dfrac{(-1)\cdot(-1)^{n}}{2n-1}$ = $(-1)^{n} \dfrac{(-1)}{2n-1}$.
    So according to Leibnitz-Criterion, if the series $ \dfrac{(-1)}{2n-1}$ is a Zero-sequence, then the alternating series converges, too.
  2. The series $\sum_{n=1}^\infty \left|\dfrac{(-1)^{n+1}}{2n-1}\right|$ = $\sum_{n=1}^\infty \dfrac{1}{2n-1}$ converges. Therefore the series is absolutely convergent.

Is this correct?


$\sum_{n=1}^\infty \frac{1}{2n-1}$ is not convergent as

$\sum_{n=1}^\infty \frac{1}{2n-1} \ge \sum_{n=1}^\infty \frac{1}{2n}$ and the series $\sum_{n=1}^\infty \frac{1}{n}$ is not convergent


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.